2017
DOI: 10.1002/ejoc.201700537
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cryptophanes in Water by Disulfide Bridge Formation

Abstract: International audienceCryptophanes are receptors consisting of two bridging concave cyclotribenzylene (CTB) subunits. The formation of cryptophanes in basic aqueous solutions (0.1 M MOD; M = Li, Na, K, and Cs) by disulfide bridge formation has been investigated. Two original CTBs, 1H(6) and 2H(6), derived from cyclotriphenolene through the introduction of mercaptomethyl and mercapto substituents, respectively, were synthesized. Cryptophane formation by slow oxygenation of 1(6-) was observed only in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 108 publications
1
7
0
2
Order By: Relevance
“…It has been shown that host 1 shows a good affinity for the K + cation and a binding constant of K ≈ 350 m –1 was measured at 278 K in LiOH/H 2 O (0.1 m ) solution by titration experiments. [3c] Other alkali cations such as Rb + and Cs + are also well recognized in LiOH/H 2 O and NaOH/H 2 O solutions by 1 and they exhibit a higher affinity for this host ( K ≈ 4 × 10 5 m –1 for Rb + and K ≈ 2 × 10 9 m –1 for Cs + ). Thus, the K + cation acts as a competitor and the affinity of guest 3 for host 1 is therefore strongly reduced under these conditions.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It has been shown that host 1 shows a good affinity for the K + cation and a binding constant of K ≈ 350 m –1 was measured at 278 K in LiOH/H 2 O (0.1 m ) solution by titration experiments. [3c] Other alkali cations such as Rb + and Cs + are also well recognized in LiOH/H 2 O and NaOH/H 2 O solutions by 1 and they exhibit a higher affinity for this host ( K ≈ 4 × 10 5 m –1 for Rb + and K ≈ 2 × 10 9 m –1 for Cs + ). Thus, the K + cation acts as a competitor and the affinity of guest 3 for host 1 is therefore strongly reduced under these conditions.…”
Section: Resultssupporting
confidence: 82%
“…In the past, these molecules have received a lot of attention because they can accommodate different atoms or molecules within their cavity. For example, it has been shown that neutral (methane, xenon, halogenomethanes) or charged (alkali cations, ammonium, anions) species can easily enter the cavity of these host molecules, depending on the cavity size and the nature of the substituents grafted on to the benzene rings , . Interestingly, the encapsulation process strongly modifies the physical properties of both the guest and host molecules, thus leading to important spectroscopic changes.…”
Section: Introductionmentioning
confidence: 99%
“…[117] Wuest and co-workers utilized the reversible dimerization of nitroso groups to form azodioxides in the synthesis of single-crystalline 3D COFs. [118] Despite being well investigated in dynamic covalent libraries, disulfide formation or exchange has only been used in avery few cases for the formation of cages, [119][120][121] and there are no examples known yet for COFs.Dynamic orthoester exchange was utilized for the formation of cryptands in the presence of appropriate templates [122] and hybrid cages were assembled through multiple Ugi four-component reactions. [123] Scheme 2.…”
Section: Dynamic Covalent Reactionsmentioning
confidence: 99%
“…[110][111][112][113][114] Da die C-C-Bindungsknüpfung in diesem Fall nur in Gegenwart eines Katalysators reversibel ist, sind solche Ansätze besonders fürd ie Synthese von stabilen Käfigen interessant. [118] Die Bildung von Disulfiden wurde nur in einigen wenigen Fällen fürd ie Bildung von Käfigen eingesetzt, [119][120][121] und fürC OFs sind bis jetzt noch überhaupt keine Beispiele bekannt, obwohl diese Reaktion fürd ynamisch-kovalente Bibliotheken gut etabliert ist. Die Polykondensation von Quadratsäure mit einem Te traaminoporphyrin führte zur Bildung eines kristallinen Squarainnetzwerks.…”
Section: Dynamisch-kovalente Reaktionenunclassified
“…[117] Wuest und Mitarbeiter nutzten die reversible Dimerisierung von Nitrosogruppen unter Bildung von Azodioxiden fürdie Synthese von einkristallinen 3D-COFs. [118] Die Bildung von Disulfiden wurde nur in einigen wenigen Fällen fürd ie Bildung von Käfigen eingesetzt, [119][120][121] [122] und Hybridkäfige konnten über mehrfache Ugi-Vierkomponentenreaktionen erhalten werden. [123]…”
Section: Dynamisch-kovalente Reaktionenunclassified